7,000 students attended UMPs Riang Ria Raya - Mimi Rabita, Abdul Wahit (2023)
PAYA BESAR, May 12, 2023 - The Riang Ria Raya event organized by Student Affairs and Alumni Department (JHEPA) was a blast with the presence of more than 7,000 students enthralled the Hari Raya Aidilfitri celebration this time.